Training for Anaerobic Differential Threshold Stand and its Impact on Lactic Acid Concentration and LDH Enzyme and VO2MaX and Cortisol Hormone for Free 400 m men-runners (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed at designing a training program by using training for the anaerobic differential threshold stand and the effects of those trainings on the variables of concentration of lactic acid and LDH enzyme, VO2 max, and cortisol hormone. The researchers used the experimental program with a one-group style. Also, they used a sample with (8) men-players in a (free 400 m men-runners), and they used many instruments and procedures, most notably the training program prepared for 10 weeks and for 3 training units weekly (70-90 min) for each unit. They used the training intensity from 85-100% of the player's ability. After finishing the training program and doing some pre-tests and post-tests and then statistically checking the results, the researchers reached many conclusions: training for the anaerobic differential threshold stand enhances the variables of the research and adjusts the player's ability to bear the training burdens.